Emergency neurosurgical hybrid operating platform for acute intracranial hemorrhage (E-HOPE) - Mingze Wang; Peicong Ge; Yuming Jiao; Xiaofeng Deng; Songlin Yu; Yuha Jiang; Zhi Li; Tao Wang; Hongwei He; Youxiang Li; Xiaolin Chen; Shuo Wang; et al. (Chinese Neurosurgical Journal)
Abstract Background Precise diagnosis and rapid treatment for acute complex intracranial hemorrhage (ICH) are crucial. The neurosurgical hybrid operating platform integrates traditional open neurosurgery operating room functionalities with endovascular therapy capabilities and is developing in the neurosurgical practice. However, its effect on the emergent complicated neurovascular cases needs pilot exploration. Methods In this prospective study, a total of 103 cases of both spontaneous and non-spontaneous ICH were consecutively recruited between June 2019 and June 2023. Demographic data, including age, gender distribution, and types of hemorrhage, were collected. Surgical interventions were tailored based on DSA, including spontaneous and non-spontaneous hemorrhages. Functional outcomes were assessed using the modified Rankin Scale (mRS) preoperatively and postoperatively. Results Over the study period from June 2019 to June 2023, a cohort of 103 ICH cases underwent emergency hybrid surgical treatment utilizing the E-HOPE platform. Among these cases, 88 were classified as spontaneous ICH, while 15 were non-spontaneous. The mean age at diagnosis for the entire cohort was 54.0 ± 3.7 years, with a slight predominance of male patients. Spontaneous ICH encompassed a diverse spectrum of etiologies, including arteriovenous malformations, aneurysms, arteriovenous fistulas, cavernous malformations, moyamoya disease, and cryptogenic hemorrhages. Surgical interventions were tailored to address the specific pathology. Notably, improvements in mRS scores were observed in a majority of cases, with some patients experiencing stabilization or deterioration postoperatively. Non-spontaneous cases (n = 15) were primarily iatrogenic (n = 13) due to tumors adjacent to the internal carotid artery, necessitating stent graft deployment. Surgical approaches, including stent graft deployment and middle meningeal artery embolization, were effective in managing these cases. Postoperative functional outcomes varied depending on the nature of the hemorrhage, with a subset of patients demonstrating improvement in mRS scores while others showed no significant change. Conclusions Emergency hybrid surgical treatment utilizing the E-HOPE platform offers promising outcomes for ICH patients. Tailored surgical approaches result in favorable postoperative functional outcomes, highlighting the importance of a multidisciplinary approach in managing these complex cases.